EXPLORING THE MENTAL STRUCTURE AND MECHANISM: HOW THE STYLE OF TRUTH-SEEKERS IN MATHEMATICAL PROBLEM-SOLVING? - Kurniati, Dian; Purwanto, Purwanto; As'ari, Abdur Rahman; Dwiyana, Dwiyana (Journal on Mathematics Education, 2018)
The Mathematics students who perform truth-seeking process upon solving mathematical problems were unique. Therefore, the study deems it necessary to know students’ mental structure and mechanism so that they can make the right decision by performing truth-seeking. However, no research has delved into the mental structures and mechanisms of Mathematics students, who tend to grapple with truth-seeking processes extensively. This study was explorative qualitative because the aims to describe the types of mental structure and mechanism of Mathematics students upon the truth-seeking process in solving mathematical problems. The research subjects are four Mathematics students at the University of Jember who perform truth-seeking and can communicate fluently when performing think-aloud. Their responses in the answer sheets drove the determination of research subjects' tendency in truth-seeking. Afterward, the results of think-aloud and task-based interview were put under analysis, so as to determine the types of mental structure and mechanism. The research findings have indicated that (1) all mental structures have been constructed by all research subjects and (2) two types of mental mechanism are evident among the subjects, including the process of interiorization coupled with coordination and another process encompassing interiorization, coordination, and reversal.